STUDI KONDUKTIVITAS ELEKTROLIT POLIMER KITOSAN/PVA+KOH - -, R.Putri; -, A.Maddu; -, Irzaman (Sistem Informasi, 2011)
The blend-based polymer electrolyte consisting of chitosan and polyvinyl alcohol (PVA) as host polymers and potassium hydroxide (KOH) as the complexing salt was studied. Polymerelectrolyte were obtained by the casting technique. An attempt was also made to investigate the effect of TiO2 concentration in the chitosan/PVA+KOH polymer electrolyte. The best ionic conductivity values of 1,105 x 10-2 S cm-1 at room temperature were obtained for the sample containing 35%wt of KOH and 1,210 x 10-2 S cm-1 for the sample containing 50% wt TiO2. The polymer electrolyte with good ionic conductivity properties were characterized by thermal analysis (DSC). The glass transition temperature about 75.30 Â°C for the optimum Chitosan/PVA+KOH